Identification of the Breeding-sites of important Species of Butterflies and their Natural Habitats for Future conservation in Gujarat and Rajasthan - Ahmed, Syed Irfan; Sharma†, Anchal; Rani, Sunita; Anjum, Hina; Sadique, Mohammed (Asian Journal of Biological and Life Sciences, 2016)
Studies were conducted on identification of the breeding sites of ten species of butterflies (Papilio demoleus, Eurema hecabe , Catopsilia pomona , Colias fieldii, Hypolimnas missipus, Danaus chrysipuss, E.core, Euchrysops cnejus, Catocrysops Strabo and Tarucus nara for their future conservation based on their seasonal abundance under different habitats under naturally available wild conditions in Gir Protected Areas of Gujarat. Some important behaviour such as mud-puddling, gully-bottoming, sun basking, higher flying etc. are very common activities required to understand the natural breeding phenomenon of butterflies. The study conducted in natural wild conditions in GPA revealed that all the ten species of butterflies exhibited a significantly positive response in their population built up as well as in their survival rate which may be due to the availability of optimal requirements of food and shelter in the wild-conditions of GPA. Whereas in semi-wild conditions of the AFRI Model Nursery, the butterflies are restricted within a limited area with specific number of host-plants. In addition, these areas are lack of natural water source like rivers and ponds etc, and lack of such requirements bring changes in the behavior of butterflies and indirectly exert negative influence on their life- span. Hence, the wild behaviour, pertaining to their population build up and larval feeding, of these species is somewhat restricted in AFRI- Model nursery. Thus, it proves that stress in any form acts as a deterrent factor in normal behaviour of butterfly species as observed in wild form.
Keywords: Behaviour; Breeding sites; Butterflies conservation; Habitats; Seasonal abundance; Stress